2022
DOI: 10.1080/15384047.2022.2133332
|View full text |Cite
|
Sign up to set email alerts
|

Exosomal epidermal growth factor receptor is involved in HPV-16 E7-induced epithelial-mesenchymal transition of non-small cell lung cancer cells: A driver of signaling in vivo

Abstract: Our previous studies have demonstrated that human papillomavirus (HPV)-16 E7 oncoprotein promoted epithelial-mesenchymal transition (EMT) in non-small cell lung cancer (NSCLC) cells. Moreover, recent studies have found that exosomes can mediate EMT of NSCLC cells and epidermal growth factor receptor (EGFR) is related to the progression of NSCLC. Here, we further investigated the role of exosomal EGFR in HPV-16 E7-induced EMT of NSCLC cells. Our results showed that the exosomes derived from the stable HPV-16 E7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…It has been reported that HPV-infected lung cancer cells exhibited increased proliferative and invasive ability both in vitro and in vivo. Further investigation revealed that Toll-like receptor 3 (TLR3) and epidermal growth factor receptor (EGFR) were the key factors regulating the invasion and EMT capacity of lung cancer, as the inhibition of TLR3 or EGFR expression in cancer cells would significantly attenuate HPV-mediated lung cancer development [ 45 , 46 ]. Moreover, HPV can decrease the expression of p53 in lung tumors and suppress tumor cell apoptosis via upregulation of the inhibitors of apoptosis proteins (IAPs) but downregulation of Bcl-2 homologous antagonist/killer (Bak) [ 47 ].…”
Section: Virus and Lung Cancermentioning
confidence: 99%
“…It has been reported that HPV-infected lung cancer cells exhibited increased proliferative and invasive ability both in vitro and in vivo. Further investigation revealed that Toll-like receptor 3 (TLR3) and epidermal growth factor receptor (EGFR) were the key factors regulating the invasion and EMT capacity of lung cancer, as the inhibition of TLR3 or EGFR expression in cancer cells would significantly attenuate HPV-mediated lung cancer development [ 45 , 46 ]. Moreover, HPV can decrease the expression of p53 in lung tumors and suppress tumor cell apoptosis via upregulation of the inhibitors of apoptosis proteins (IAPs) but downregulation of Bcl-2 homologous antagonist/killer (Bak) [ 47 ].…”
Section: Virus and Lung Cancermentioning
confidence: 99%
“… 11 Human papillomavirus can enhance the expression of EGFR in exosomes, which is involved in the epithelial-mesenchymal transition (EMT) of lung cancer cells. 12 In lung cancer, EGFR-containing exosomes can also regulate the function of T cells. 13 Moreover, EGFR in breast cancer cell-derived exosomes can activate the mitogen-activated protein kinase (MAPK) survival pathway and stimulate monocyte survival.…”
Section: Introductionmentioning
confidence: 99%
“…Human papilloma virus (HPV) is a known cause of human cancer, and has been shown to be associated with multiple sites of human cancer, such as cervix, reproductive tract, skin, head and neck, oropharynx and other sites ( Szymonowicz & Chen, 2020 ; De Martel et al, 2017 ; Serup-Hansen et al, 2014 ; Corredor et al, 2022 ). The latest research shows that HPV infection plays a key role in the occurrence and development of Lung carcinoma (LA), especially in non small cell lung carcinoma (NSCLC) ( Zhou et al, 2022 ). High risk human papillomavirus (HR-HPV) will produce HPV oncoproteins E6 and E7 after infecting cells.…”
Section: Introductionmentioning
confidence: 99%